2017
DOI: 10.7717/peerj.3249
|View full text |Cite
|
Sign up to set email alerts
|

The genetics of venom ontogeny in the eastern diamondback rattlesnake (Crotalus adamanteus)

Abstract: The same selective forces that give rise to rapid inter- and intraspecific divergence in snake venoms can also favor differences in venoms across life-history stages. Ontogenetic changes in venom composition are well known and widespread in snakes but have not been investigated to the level of unambiguously identifying the specific loci involved. The eastern diamondback rattlesnake was previously shown to undergo an ontogenetic shift in venom composition at sexual maturity, and this shift accounted for more ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 50 publications
1
32
0
2
Order By: Relevance
“…Intraspecific toxin variation has been subject to diverse studies on trophically venomous species that have demonstrated how a venom's composition and bioactivity may differ between populations (e.g. Amazonas et al, 2018), sexes (Rash, King & Hodgson, 2000), and ontogenetic stages (Rokyta et al, 2017). Animal venoms primarily utilized in prey subjugation often evolve under strong positive selection and allow for evolutionary tinkering, resulting in higher compound variability.…”
Section: Discussionmentioning
confidence: 99%
“…Intraspecific toxin variation has been subject to diverse studies on trophically venomous species that have demonstrated how a venom's composition and bioactivity may differ between populations (e.g. Amazonas et al, 2018), sexes (Rash, King & Hodgson, 2000), and ontogenetic stages (Rokyta et al, 2017). Animal venoms primarily utilized in prey subjugation often evolve under strong positive selection and allow for evolutionary tinkering, resulting in higher compound variability.…”
Section: Discussionmentioning
confidence: 99%
“…We isolated RNA via a standard TRIzol extraction following Rokyta et al . 20 , 44 , 45 . Briefly, venom glands were finely diced and placed in TRIzol solution (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
“…Extender assemblies used 1000 merged reads as seeds, extending the seeds based on exact overlaps of 120 base pairs. This method has efficiently assembled toxin sequences in a variety of snake taxa, including other Crotalus species 19 , 20 , 44 , 45 , 48 50 . De novo NGen assemblies were performed with default settings in NGen v. 14.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations